ADABU THALIB (ADAB SEORANG PELAJAR): ETIKA SEORANG PENUNTUT ILU - Bani Rif'ai, Deden; Fateh Al Muhibbin; Wahyu Al Karim Uszajalli; Muhammad Jundi Abdullah Robbaniy; Muhammad Akmansyah (STIT Pringsewu, 2024)
This abstract discusses the concept of adab in seeking knowledge, focusing on the term